PROTECTIVE EFFECT OF BEE PROPOLIS AGAINST ANTI-TUBERCULOSIS DRUGS (RIFAMPICIN AND ISONIAZID)-INDUCED HEMATOLOGICAL TOXICITY IN SPRAGUE DAWLEY RATS - Bharti, Umesh; Kumar, Neelima R; Kaur, Jaspreet (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: Protective effect of bee propolis against anti-tuberculosis (TB) drugs (rifampicin and isoniazid)-induced hematological toxicity in Sprague Dawley (SD) rats. Methods: Experimental male SD rats weighing 180Â±20 g were randomly assigned into eight groups (n=6), the Group 1 served as control; Group 2 received 200 mg bee propolis/kg body weight; Groups 3, 5, and 7 were treated with drugs 100 mg rifampicin/kg body weight, 50 mg isoniazid/kg body weight, and 100 mg rifampicin+50 mg isoniazid/kg body weight, respectively. Groups 4, 6, and 8 were treatment groups receiving 200 mg bee propolis/kg body weight+100 mg rifampicin/kg body weight, 200 mg bee propolis/kg body weight+50 mg isoniazid/kg body weight, and 200 mg bee propolis/kg body weight+100 mg rifampicin+50 mg isoniazid/kg body weight, respectively. All the treatments were given for 30 days, and then, the rats were sacrificed under light esthesia by cervical dislocation and blood was collected for physiological studies. Results: Bee propolis supplementation (200 mg/kg body weight) showed increased level of hemoglobin with respect to rifampicin (15.45%), isoniazid (11.34%), and rifampicin plus isoniazid (5.04%) administered groups after 30 days of treatment. Moreover, the decreased level of red blood cell count and white blood cell count by anti-TB drugs rifampicin, isoniazid, and rifampicin plus isoniazid together was also elevated in treatment group with bee propolis. Conclusion: Coadministration of propolis (200 mg bee propolis/kg body weight) with drugs helped modulate the toxic effects by restoring tested values to near normal. Keywords: Propolis, Rifampicin, Isoniazid, Hemoglobin, Red blood cell count, White blood cell count.